Tribology in machine design - Stolarski, T. A. (Heinemann Newnes, 1990)
Tribology in Machine Design aims to promote a better appreciation of the increasingly important role played by tribology at the design stage in engineering. This book shows how algorithms developed from the basic principles of tribology can be used in a range of practical applications. The concept of tribodesign is introduced in Chapter 1. Chapter 2 is devoted to a brief discussion of the basic principles of tribology, including some concepts and models of lubricated wear and friction under complex kinematic conditions. Elements of contact mechanics, presented in Chapter 3, are confined to the.